Sleep and physical activity: results from a long-term actigraphy study in adolescents - Chiara E. G. Castiglione-Fontanellaz; Tammy T. Timmers; Stefan Lerch; Christoph Hamann; Michael Kaess; Leila Tarokh (BMC, 2022)
Abstract Purpose Research to date suggests that physical activity is associated with improved sleep, but studies have predominantly relied on self-report measures and have not accounted for school day/free day variability. To address these gaps in the literature, the aim of the present study was to (a) quantify physical activity in adolescents using long-term daily actigraphy measurement and (b) to examine the association between actigraphically assessed steps and sleep behavior in a sample of healthy adolescents. To be able to capture intra- and inter-individual differences in the daily physical activity of adolescents, we examined within as well as between subjects effects and its association with sleep. Methods Fifty adolescents between 10 and 14 years of age were included in the present study. In total 5989 days of actigraphy measurement (average of 119 ± 40 days per participant; range = 39-195 days) were analyzed. We use multilevel modeling to disentangle the within and between subject effects of physical activity on sleep. In this way, we examine within an individual, the association between steps during the day and subsequent sleep on a day-to-day basis. On the other hand, our between subjects' analysis allows us to ascertain whether individuals with more overall physical activity have better sleep. Results Within a subject more steps on school and free days were associated with later bed times on school and free days as well as later rise times on school days only. On the other hand, comparing between subjects' effects, more steps were associated with lower sleep efficiency on free and school days. No other significant associations were found for the other sleep variables. Conclusion Our results obtained through objective and long-term measurement of both sleep and number of steps suggest weak or non-significant associations between these measures for most sleep variables. We emphasize the importance of the methodology and the separation of within subject from between subject features when examining the relationship between physical activity and sleep.